Identification of Endophytic Fungi on Healthy and Disease Stem of Vanilla Plants (Vanilla planifolia) Caused by Stem Rot Disease - Yuliana Yuliana; Achmad Himawan; Elisabeth Nanik Kristalisasi (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
One of the plantation crops with high economic value is vanilla. The biggest constraint in vanilla cultivation is stem rot disease. Endophytic fungi are fungi that live inside healthy plant tissues without causing symptoms or damage to the host plant. This study was aimed at determining the percentage of vanilla stem rot disease caused by the fungus Fusarium oxysporum f.sp. vanilla, identifying and selecting the type and amount of endophytic fungi found in healthy vanilla plants and vanilla plants with mild, moderate, and severe symptoms of stem rot. The research was carried out in a vanilla plantation belonging to the residents of Sinogo Village, West Plono Village, and West Ngalian Samigaluh Village, Kulon Progo, Yogyakarta from January to March 2021. The research method used was a descriptive method for symptoms of the disease. A survey and collection of healthy stems and stem rot disease were then conducted. In addition, environmental conditions such as air temperature, humidity, sunlight intensity, and soil pH were also recorded. Identification of endophytic fungi was carried out in the laboratory. The data were analyzed both quantitatively (percentage of disease attack) and qualitatively (morphological characteristics of fungi macroscopically and microscopically). The results showed that the percentage of vanilla stem rot disease from the largest to the smallest was 30% in West Plono Village, 25.3% in West Ngalian Village, and 22.8% in Sinogo Village. In healthy vanilla plants, there are 4 types of endophytic fungi: Aspergillus niger, Cladosporium sp., Penicillium sp., and Trichoderma sp. In vanilla stem rot disease, 2 types of endophytic fungi were found, Aspergillus niger and Cladosporium sp.